The relative dependence of Spanish landscape pattern on environmental and geographical variables over time - Ortega, M.=700 1 Bunce, R.G.H.; Garcia del Barrio, J.M.; Elena Rosello, R.
(En, Es)
ilus., 38 ref.
Keywords: CAMBIO CLIMATICO; EFECTO INVERNADERO; CARACTERISTICAS DEL SITIO; PAISAJE; COMPOSICION BOTANICA; GEOGRAFIA; ESPAÑA; INVESTIGACION AGRARIA: SISTEMAS Y RECURSOS FORESTALES